The burden of bites and stings management: Experience of an academic hospital in the Kingdom of Saudi Arabia - Anas Khan; Waad H. Al-Kathiri; Bander Balkhi; Osama Samrkandi; Mohammed S. Al-Khalifa; Yousef Asiri (Saudi Pharmaceutical Journal)
Purpose: The main aim of this study is to estimate the economic burden and prevalence of bites and stings injuries in Saudi Arabia. Methods: A retrospective, cross-sectional study was conducted at King Saud University Medical City (KSUMC) for all bites and stings cases presented to the Emergency Department (ED) between the period June 2015 and May 2019. Results: A total of 1328 bites and stings cases were treated in the ED at KSUMC. There were 886 insect bites and stings cases, 376 animal bites, 22 human bites, 34 scorpion stings, and ten snakebites. Most cases were reported in April - June. Females account for 62% of the reported cases, and the mean age was 24 years old. The total management cost of bite and sting cases during the study period was 3.4 million Saudi Riyal (SR). The spending cost of the management of animal bites was the highest as it cost 1,681,920.76 SR, followed by insect's management costing 1,228,623.68 SR. Conclusion: Bites and stings have a considerable health care burden on our society. Although the vast majority of the cases were not associated with a severe life-threatening condition, many were visit ED and associated with high medical costs. Increased awareness of the hazards of animal-related injuries, especially during spring and summer, where most cases take place may lower its incidence and decrease EDs visits.